2019
DOI: 10.1111/acel.12938
|View full text |Cite
|
Sign up to set email alerts
|

Decoy fitness peaks, tumor suppression, and aging

Abstract: Recent reports by Martincorena et al and Yokoyama et al reveal unanticipated dynamics of somatic evolution in the esophageal epithelium, with clonal expansions apparently driven by mutations in Notch1 dominating the epithelium even in middle‐aged individuals, far outpacing the prevalence of these mutations in esophageal cancers. We propose a model whereby the promotion of clonal expansions by mutations such as in Notch1 can limit more malignant somatic evolutionary trajectories until old ages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Inactivation of NOTCH1 has been postulated to drive the evolutionary dead-end of nascent precancerous population of cells (Higa and DeGregori). This is based on the observation that the frequency of NOTCH1 mutations decreases in esophageal and skin cancers, relative to physiologically normal epithelial tissues (Higa and DeGregori, 2019;Martincorena et al, 2018;Yokoyama et al, 2019). Consistent with this, in our previously reported Onc3 screen, we noted that the frequency of Notch1 inactivation was decreased in cuSCC versus keratoacanthoma tissues, suggesting that Notch1 loss is not essential for cuSCC development (Aiderus et al).…”
Section: Discussionsupporting
confidence: 81%
“…Inactivation of NOTCH1 has been postulated to drive the evolutionary dead-end of nascent precancerous population of cells (Higa and DeGregori). This is based on the observation that the frequency of NOTCH1 mutations decreases in esophageal and skin cancers, relative to physiologically normal epithelial tissues (Higa and DeGregori, 2019;Martincorena et al, 2018;Yokoyama et al, 2019). Consistent with this, in our previously reported Onc3 screen, we noted that the frequency of Notch1 inactivation was decreased in cuSCC versus keratoacanthoma tissues, suggesting that Notch1 loss is not essential for cuSCC development (Aiderus et al).…”
Section: Discussionsupporting
confidence: 81%
“…One interpretation of these data is that competition with other mutant clones restrains Trp53-mutant cell proliferation. It may be possible, therefore, that the accumulation of somatic mutations with age has a role in preventing the clonal expansion of cells with increased fitness through tumoursuppressive competition (Higa and DeGregori, 2019).…”
Section: Anti-tumourigenic Rolesmentioning
confidence: 99%
“…Another important finding was though mutations connected to benign clonal expansion may appear frequently in cancer cell genomes, these particular mutations may not necessarily contribute to carcinogenesis because these tissues already have a naturally high mutation frequency. Furthermore, an analysis by Higa and DeGregori demonstrated that even classic “oncogenic drivers” like NOTCH1 might not often contribute to carcinogenesis [ 18 ].…”
Section: Clonal Development Circulating Tumor Dna and Cancer Detectmentioning
confidence: 99%